THE EFFECTIVENESS OF GOOD INTERVIEW FOR STUDENTS' MOTIVATION IN LEARNING SPEAKING - Luluk Setyowati (STKIP PGRI Jombang, 2019)
THE EFFECTIVENESS OF GOOD INTERVIEW FOR STUDENTS' MOTIVATION IN LEARNING SPEAKINGSpeaking skill is an important skill that they should master when they learn a language. Based on the observation, speaking ability of Student of Politeknik Kelapa Sawit Bekasi still in low level. The students seem to be confused to express their idea using English, mainly because of the lack of vocabulary. In this study, the researcher attempts to conduct a research about the use of students’ good interview in English language classrooms and its impact in speaking skill. The use good interview in classroom is important because of its positive impact on students’ proficiency level. The objective of this research was to prove whether or not students’ motivation in speaking learning can be improved by using good interview for students in Cultivation Program of Politeknik kelapa Sawit Bekasi The results of this study shows that before the implementation of good interview, students speaking skills are in low level. However, after doing good interview, students felt greatly helped by the good interview material, unlike other boring speaking material and told them to do public speaking, good interviews were felt to provide them with many benefits, so they are felt motivated and eager to learn speaking more.